2006
DOI: 10.1002/em.20254
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of bleomycin‐induced incomplete chromosome elements in two mammalian cell lines using a telomeric PNA probe

Abstract: Fluorescence in situ hybridization (FISH) with a telomeric peptide nucleic acid probe was employed to analyze the induction of incomplete chromosome elements (ICE; i.e., incomplete chromosomes and terminal fragments) by bleomycin (BLM) in two mammalian cell lines. Chinese hamster embryo cells (CHE cell line, average 2n = 23) and domestic rabbit cells (CPC cell line, average 2n = 44) were treated with 2.5 micro g/ml BLM; after 18 hr of incubation, first-division metaphases were stained with the telomeric probe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…1A). On the other hand, the high spontaneous frequency of IC and acentric fragments observed in control cells (Table 1a) cannot be linked to the results of the FISH analysis and is similar to that found in other mammalian cell lines, previously investigated in our laboratory for telomere instability [17,[30][31][32]. Furthermore, the significant increase in the frequency of telomere FISH signal loss found in control cells 10 and 15 days after treatment (Table 1b) could be due to spontaneous extensive telomere shortening, a phenomenon usually observed in in vitro cultured cells [1][2][3][4].…”
Section: Chromosome Damage and Distribution Pattern Of Telomeric Sequsupporting
confidence: 76%
“…1A). On the other hand, the high spontaneous frequency of IC and acentric fragments observed in control cells (Table 1a) cannot be linked to the results of the FISH analysis and is similar to that found in other mammalian cell lines, previously investigated in our laboratory for telomere instability [17,[30][31][32]. Furthermore, the significant increase in the frequency of telomere FISH signal loss found in control cells 10 and 15 days after treatment (Table 1b) could be due to spontaneous extensive telomere shortening, a phenomenon usually observed in in vitro cultured cells [1][2][3][4].…”
Section: Chromosome Damage and Distribution Pattern Of Telomeric Sequsupporting
confidence: 76%
“…Chromosomal aberrations involving the chromosome ends or the telomeric sequences located at the chromosome ends Several publications refer to the application of telomere FISH to analyse the induction of ICEs and IFs by low-and high-LET radiations and chemical mutagens (51,(58)(59)(60)(61)89,90,92,(128)(129)(130)(131)(132)(133) [see (1,39) for review]. These studies include the analysis of all types of asymmetrical chromosome aberrations induced by ionising radiation and the radiomimetic compound bleomycin in human lymphocytes and the ones induced by this compound and the antibiotics streptonigrin and streptozotocin in Chinese hamster cells.…”
Section: Induction Of Chromosomal Aberrations Involving Telomeres And...mentioning
confidence: 99%
“…It was found that the main form of ICEs (Figure 2) induced by clastogenic agents-irrespective of their mode of action-consists of pairs ICs þ TFs (Figure 2A, Case 1) (59,(128)(129)(130)(131). The predominance of some form of ICE over the other ones might be explained by the attachment of the telomeres to the nuclear matrix [see (1) for discussion].…”
Section: Induction Of Chromosomal Aberrations Involving Telomeres And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The abovementioned studies, perfomed using FISH with a Peptide Nucleic Acid telomere probe (telomere PNA-FISH) in Chinese hamster cells (CHE cell line), showed that all the above drugs can induce the formation of incomplete chromosomes and terminal fragments [55][56][57][58].…”
Section: Bleomycin (Blm) Streptonigrin (Sn) and Streptozotocin (Stz)mentioning
confidence: 99%